Selecting tools to enhance scholarly communication through the life cycle of scientific research - Olena Kuzminska (Academy of Cognitive and Natural Sciences, 2021)
Education and science digitalization belongs to the priority areas of information society development. However, we can observe that while Ukraine enters the European educational and scientific space, Ukrainian scientists cannot yet efficiently compete in the international labor market. One of the reasons behind this is that Ukrainian scientists and researchers are not fully integrated into the world system of digital scholarly communication. To help researchers use digital tools supporting scholarly communication, many companies carry out various educational events to support open science and initiate international research and projects. Under modern conditions the digitalization of scientific communication went to the front-burner due to the COVID-19 pandemic. At the same time, the forced transition to digital scholarly communications through the COVID-19 pandemic can help integrate young scientists into the international scientific space. This article provides an analysis of tools to support scholarly communication developed within the "101 Innovations in Scholarly Communication" project. The international survey demonstrates the tools that scientists prefer to use at each stage of the research. This paper characterizes the advantages of particular tools on different stages of scientific research process induced by the current tendency for scholarly communication digitalization. During the work, we outlined the scope for future research and found it necessary to conduct an additional survey for the scholarly community.